Ultrastructural study on the fertilisation process in sturgeon (Acipenser), function of acrosome and prevention of polyspermy - Psenicka, Martin; Rodina, Marek; Linhart, Otomar (Animal reproduction science, 2010)
Sturgeon gametes differ from other fish in that their spermatozoa possess acrosome with finger-like posterolateral projections, which undergo exocytosis and filament formation, whereas eggs possess numerous micropyles. The fertilisation process in Acipenser baerii was investigated by fluorescence and electron microscopy. A suitable activation solution containing 2.5 mM CaCl(2), 15 mM Tris, pH 10 was found for detailed description of acrosomal reaction. The acrosome reaction includes the formation of a spear-like fertilisation filament coming from three endonuclear canals and implantation fossa through the acrosomes. It can accelerate the process of polyspermy prevention. Another unique feature of the acrosome was an anchor-like opening of the posterolateral projections. Mature eggs of A. baerii possessed 2-10 micropyles in the animal pole region. The eggs consisted of three principal layers and an outermost jelly coat blocking micropyle, and a layer of cortical granules in unfertilised eggs. With the exposure to freshwater, the jelly like layer separated from the egg surface, whereas the cortical granules swelled. No change between the layers of fertilised and unfertilised eggs, apart from the generation of an increasing perivitelline space by dissolution of the cortical granules, had been observed after the fusion of spermatozoon with an egg. A fertilisation cone blocked a fusion of other spermatozoa with cytoplasmatic projection in the fertilised micropyle.
Keywords: Ovum; ovum; Male; akrozom; fluorescenční mikroskopie; Fertilization; Spermatozoa; mužské pohlaví; ryby; Acrosome; Fishes; Animals; Microscopy, Fluorescence; ženské pohlaví; Microscopy, Electron, Transmission; Microscopy, Electron, Scanning; zvířata; spermie; Female; mikroskopie elektronová rastrovací; transmisní elektronová mikroskopie; fertilizace